2020
DOI: 10.21203/rs.3.rs-49568/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Larval Metal Pollutant Exposure Alters the Epigenetic Architecture of the Major Malaria Vector Anopheles Arabiensis (Diptera: Culicidae)

Abstract: BackgroundAnopheles arabiensis (a member of the An. gambiae species complex) is a major vector of malaria. These mosquitoes typically breed in clean bodies of water, but can also utilise polluted waters. Although this expands their breeding range, adaptation to breeding in polluted waters necessitates coping with a large amount of environmental stress in the form of exposure to heavy metal pollutants. Environmental stress can induce heritable changes to an organism without altering the basal genetic code. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The study of anthropogenically derived influences as epigenetic stimuli, such as pollution and climate change, are among the fast-growing areas of interest within insect EMMs [ 79 , 80 , 81 ]. The goal of these studies is to assess how stressors may affect different ecological levels [ 82 ], considering exposure to pesticides [ 41 , 44 , 83 ], endocrine disruptors [ 11 , 84 , 85 ], heavy metals [ 84 , 86 , 87 ], or temperature changes [ 88 ] as triggers of epigenetic changes. In Table 2 , we summarize the different responses of insect biology to different kinds of toxicants and whether there is evidence of the role of EMMs in these processes.…”
Section: Epigenetic Molecular Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of anthropogenically derived influences as epigenetic stimuli, such as pollution and climate change, are among the fast-growing areas of interest within insect EMMs [ 79 , 80 , 81 ]. The goal of these studies is to assess how stressors may affect different ecological levels [ 82 ], considering exposure to pesticides [ 41 , 44 , 83 ], endocrine disruptors [ 11 , 84 , 85 ], heavy metals [ 84 , 86 , 87 ], or temperature changes [ 88 ] as triggers of epigenetic changes. In Table 2 , we summarize the different responses of insect biology to different kinds of toxicants and whether there is evidence of the role of EMMs in these processes.…”
Section: Epigenetic Molecular Mechanismsmentioning
confidence: 99%
“…Over half of the studies shown in Table 2 were conducted on dipterans as model organisms, with considerable focus on species with aquatic phases during development such as mosquitoes (e.g., [ 11 , 84 , 132 ]). Of all the toxicants reviewed, the only group without studies in aquatic environments is the carbamate cholinesterase inhibitors, a group of organic compounds derived from carbamic acid (NH 2 COOH) found in broad-spectrum pesticides (e.g., [ 107 , 108 , 109 , 110 ]).…”
Section: Epigenetic Molecular Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations